Secondary Hemophagocytic Lymphohistiocytosis - Nanwani, Poonam; Khan, Zoya; Yadav, Ashok (Annals of Pathology and Laboratory Medicine, 2020)
Introduction : Hemophagocytic lymphohistiocytosis (HLH) is a rare hematological disorder which may be fatal due to uncontrolled activation of immune system. It is characterized by hemophagocytosis in bone marrow, liver or lymph nodes along with presence of fever, pancytopenia, splenomegaly. It has been associated with bacterial, viral, fungal and parasitic infection. The study aims to explore the utility of bone marrow aspiration in patients with pancytopenia and bicytopenia which supports the diagnosis in a scenario where there is clinical suspicion of HLH. Material and Methods – prospective study carried out in department of pathology from August 2018 to July 2019. We studied 88 cases of pancytopenia and bicytopenia. All relevant clinical history and investigations were collected. Bone marrow aspiration done and smears were studied in all the cases. Result – Out of 88 cases studied 28 patients were having bicytopenia and 60 were having pancytopenia with male to female ratio 13 :9.Out of these 88 patients we reported 3 patients as having HLH who fulfill the criteria according to Revised Diagnostic Guidelines for hemophagocytic lymphohistiocytosis (HLH). Conclusion :-An early diagnosis and treatment is the key to decrease the mortality caused by this dreadful disease and if left undiagnosed and undertreated, Hemophagocytic lymphohistiocytosis can be rapidly progressive and potentially fatal.